New Approaches in Taxonomy Representatives of Rickettsiales Order - S. N. Shpynov (Эпидемиология и вакцинопрофилактика, 2016)
Systematics and nomenclature of representatives Rickettsiales order has always been based on a limited number of available phenotypic characteristics, due to their obligate intracellular localization. Intensive use of «molecular» technology has led to the description of a large number of new species of this taxonomic group, as well as to the reclassification of some of its representatives. Another symbol of the era of «molecular» technology is the emergence of species, genera and families with candidate status («Candidatus») due to the inability of cultivation and studying of biological properties that is required for a valid description of the new species. It should be a legitimate solution to this problem, based on the development and application of new high technologies. This review summarizes recent data on the taxonomy, nomenclature and evolution of representatives order Rickettsiales, new technologies, approaches and methods for the study of certain groups of prokaryotes. Published materials were obtained in the analysis of foreign and Russian scientific publications, as well as on the basis of its own published data. The paper contains a new understanding of the classification within the genus Rickettsia.